Power Consumption Modeling based on Real-Time Data Traffic for Balancing Power Supply and Energy Demand to Develop Green Telecommunication Tower: A Case Study - Abdulmula, A. M. O.; Sopian, K.; Haw, L. C. (Engineering, Technology & Applied Science Research, 2019)
Green telecommunication tower primarily depends on renewable energy and energy efficiency technologies. This study presents a power consumption model to estimate the load demand of a telecommunication tower (TT) to improve energy efficiency. The method is based on field measurements of real-time data traffic load of the entire operated macrocell telecommunication tower to balance power supply and energy demand. This advanced method is investigated using HOMER Pro simulation and compared with a widely accepted technique called overall peak load method for a chosen case study. The comparison simulation results showed that by using the power consumption model method, the energy-saving efficiency at the TT is improved by 24.19% and the size of the overall system is decreased by 33.33%. Consequently, the annualized cost is reduced by 25.7%. This optimum performance contributes to the effective development of green telecommunication towers.